2013
DOI: 10.1002/fuce.201300153
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential Tape Casting of Anode‐Supported Solid Oxide Fuel Cells

Abstract: A novel route was developed to fabricate anode‐supported solid oxide fuel cells with a high throughput and low manufacturing costs. In contrast to classical manufacturing routes, this novel route starts with the tape casting of the thin electrolyte followed by the tape casting of the anode and anode support. All three layers were cast green‐on‐green and finally sintered to yield a gas‐tight electrolyte. By carefully selecting the raw materials for all three layers, it is possible to manufacture near‐net‐shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
1
35
1
2
Order By: Relevance
“…In these experiments the stress in the electrolyte layer and in the free surface of the anode was measured, yielding values between -710 MPa and -642 MPa for the electrolyte surface and -100 MPa and -90 MPa for the free surface of the anode for the flattened and nonflattened cells, respectively. From the new results it is clear that the stress reported in [44] for the Type-IV cells corresponds to the stress of the YSZ phase in the free surface of the anode and not to the electrolyte stress and that overall similar electrolyte stresses exist in Type-III and Type-IV cells. This text replaces partly the third bullet point on page 101 and widens the explanations given on page 102 paragraphs (i) to (v).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In these experiments the stress in the electrolyte layer and in the free surface of the anode was measured, yielding values between -710 MPa and -642 MPa for the electrolyte surface and -100 MPa and -90 MPa for the free surface of the anode for the flattened and nonflattened cells, respectively. From the new results it is clear that the stress reported in [44] for the Type-IV cells corresponds to the stress of the YSZ phase in the free surface of the anode and not to the electrolyte stress and that overall similar electrolyte stresses exist in Type-III and Type-IV cells. This text replaces partly the third bullet point on page 101 and widens the explanations given on page 102 paragraphs (i) to (v).…”
mentioning
confidence: 76%
“…The explanation for the obtained residual stress results for the various types of anode-supported SOFCs should be widened by the following text: Results obtained on the residual stresses in the electrolyte layers were summarized in section 3.2.4 of [44]. Considered were different cell types that were manufactured either via the classical or the sequential tape casting route (type IV).…”
mentioning
confidence: 99%
“…Anode-supported solid oxide fuel cells (SOFCs) have been proposed as applicable SOFCs with higher power densities, since thinner electrolytes are available for these anode-supported cells [1][2][3][4][5][6][7][8][9][10]. However, it has been reported that other problems emerge for these anode-supported fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Here we report the results of al ong-term test using as hort stack with anode-supported cells that recently attained ac ontinuous operation time of 70 000 h( eight years)-the longest operation time ever reached for this technology and almost twice the operation time required for economical, long-term stationary applications.T he stack was operated using humidified hydrogen at 700 8Ca nd ac urrent density of 0.5 Acm À2 .T he anode-supported SOFC variant exhibits superiore lectrochemical per-formance and can also be operatedu sing natural gas at relatively low temperatures. [12] Thus,long-term stability is an important indicatoro ft he technologys developmental status and ak ey prerequisite for its successful commercialization.In seekingt or ealizet his and enhance the performance of anode-supported cells,s cientists at the Forschungszentrum Jülich have been conducting long-running research on materials and manufacturing technology [13,14] and the development of steel for interconnector plates. Our record-breaking result represents am ajor leap forward for this technology and is likely to stimulate renewed researchi nt his area.…”
mentioning
confidence: 99%
“…In seekingt or ealizet his and enhance the performance of anode-supported cells,s cientists at the Forschungszentrum Jülich have been conducting long-running research on materials and manufacturing technology [13,14] and the development of steel for interconnector plates. [15] Thej oining and sealing materials have been one key aspect of materials research, given the decisive role these play in thermal cycling and stack reliability.…”
mentioning
confidence: 99%